Taxonomy and new collections of wild potato species in Central and Southern Peru in 1999 - Salas, Alberto R.; Huamán, Zósimo; Hijmans, Robert J.; Torres Maita, Rafael Vinci; Hoesktra, Roel; Schüler, Konrad (Springer Nature, 2025)
Peru contains about half of the described wild potato taxa, and many of these are not yet preserved in genebanks. This paper reports results of the second of a series of five planned collecting expeditions to Peru. Collections were made in the central Peruvian departments of Ancash, Huancavelica, La Libertad, and Lima, from March 8 to April 25,1999. They follow collections in 1998 in the southern Peruvian departments of Apurimac, Arequipa, Cusco, Moquegua, Puno, and Tacna. We collected 101 germplasm accessions, including first germplasm collections of the following 22Solanum taxa:Solanum amayanum, S. anamatophilum, S. arahuayum (lost in germplasm increase),S. augustii, S. bill- hookeri, S. cantense, S. chavinense, S. chomatophilum var. subnivale, S. chrysoflorum, S. gracilifrons, S. hapalos um, S. huarochiriense, S. hypacrarthrum, S.jalcae, S. moniliforme, S. multiinterruptum f. longipilosum, S. multiinterruptum var. machaytambinum, S. peloquinianum, S. rhombilanceolatum, S. simplicissimum, S. taulisense (lost in germplasm increase), andS. wittmackii. In addition, new collections were made of the under-collected speciesS. hastiforme (three collections). The above taxonomy is that used in planning our expedition, that we compare to a new treatment of Peruvian wild potatoes published by C. Ochoa in 1999. This paper reports the collection and new species identifications of the 1999 collections, and germplasm conservation and survival of the 1998 and 1999 collections. In addition, chromosome counts are provided for 134 accessions from the 1998 and 1999 expeditions, including first reports forS. chomatophilum var. subnivale (2n = 2x = 24),S. megistacrolobum subsp.purpureum (2n = 2x = 24), andS. multiinterruptum var.multiinterruptum f.albiflorum (2n = 2x = 24); we also report the first triploid count of an accession ofS. immite.